IMPACT OF PROPAGATION PARAMETERS ON ENERGY EFFICIENCY IN VIRTUAL MIMO-BASED WIRELESS SENSOR NETWORK - Eni Dwi Wardihani; Wirawan Wirawan; Gamantyo Hendrantoro (Universitas Trunojoyo Madura, 2014)
IMPACT OF PROPAGATION PARAMETERS ON ENERGY EFFICIENCY IN VIRTUAL MIMO-BASED WIRELESS SENSOR NETWORK a,bEni Dwi Wardihani, aWirawan, aGamantyo Hendrantoro aDept. of Electrical Engineering, Institut Teknologi Sepuluh Nopember, Surabaya, 60111 b Dept. of Electrical Engineering, Politeknik Negeri Semarang, Semarang, E-mail : edwardihani@gmail.com Abstract Propagation parameters, i.e. transmission distance, constellation size and channel path loss exponent, dictate the design of energy efficient transmision techniques for WSN. In this paper, by considering these parameters we investigate to obtain the best modulation scheme and transmission strategy that minimizes the total energy consumption of the network, comprised of transmission energy and circuit energy. Analysis of virtual MIMO systems, where the sensor with a single antenna are cooperating to send the data to the Fusion Center (FC) having multiple antenna, for WSN with Alamouti-diversity scheme-based is presented, which has better spectrum efficiency but larger circuit energy consumption than Single Input Single Output (SISO) systems. Our study shows that in certain transmission distance with appropriate selection of constellation size, virtual MIMO systems for WSN have better energy efficient than SISO and Multi Input Single Output (MISO). . Key words: propagation, energy, efficiency, MIMO, sensor networks.